Isang feministang pagbasa kay B.S. Medina, Jr. - Nicolas, Alice Gregorio (Animo Repository, 1997)
This study aims to find out the attitude of the Filipino fiction writer, Dr. Buenaventura S. Medina, Jr. towards women through his writings. Among his writings included in this study are two of his novels (Alaga and Moog), a collection of short stories (Fifties), two collection of essays (Ang Tao sa Kwadro and Pintig), and a collection of his prize winning works (Gantimpala). In order to examine Medina's feminist views, the following questions were poised:What is the role of women characters in Medina's novels and short stories?How did Medina use the image of women (or of woman) in her relations with other character roles, particularly, male roles?How did Medina use language (or words) in describing women as they think, say, act?How does Medina view women in his translating work?In his presentation of findings, the author made the following observations:In Medina's novels, his women characters are under the power of his men characters.In his essays, Medina views women as meek, weak, and beautiful they serve only to answer mens' needs and to please society's dictates.Medina's women roles are confined to wifely duties such as conceiving and giving birth, cleaning, cooking, caring for husband and children, waiting for her destiny, whether in life or in love.In his translation works, Medina favored male themes. He paid very little attention to women, their experiences, thoughts, and ways of life. If Medina as a writer of influence can manipulate the mind of this readers, his views on women can certainly influence their thinking. His image of women as weak, emotional, docile, and unempowered speaks of his sexist attitude against women. On the other hand, his male characterization gives the impression that he favors men and all that his masculine image projects.Based on his work, the author recommends more psychoanalytic studies into the writings of B.S. Medina in support of his theory, and further studies on Medina as a literary critic-scholar. Other recommendations include a complete listing of his works in such libraries as The National Library, and those of UP, Ateneo and De La Salle University the holding of an extensive interview of the writer for a better understanding of his works, and the inclusion of this writings among the required course readings in class to enable young readers to appreciate his works.